Correlation Between Iodine Status and Dysfunctional Parameters of the Thyroid Gland of Djidja Schoolchildren - Alphonse S. Avocefohoun; Bertin A. Gbaguidi; Haziz Sina; Olivier Biaou; Adolphe Adjanohoun; Christophe S. Houssou; Lamine Baba-Moussa (European Scientific Journal, ESJ, 2018)
Iodine is reported to be one of the main trace mineral constituting thyroid hormones. The aim of this study was to determine the correlation between urinary iodine concentration status and dysfunctional parameters of the thyroid gland of schoolchildren in central Benin. In our study we selected 108 schoolchildren to whom we performed T3, T4, TSH, iodine and thyroid volume tests. The determination of the morning urinary iodine (iodine) in Djidja schoolchildren gave satisfactory results to 72% thus declaring our study area as a zone of non-iodine dietary deficiency. The hormone assay results are favorable at a rate of 92% and corresponds to hypothyroidism. In fact, TSH are high in 85% of the study population, T3 are in their case low in 93% of our study population and finally T4 are lower in the 100% of individuals in the study population. But these results are not in agreement with the iodine obtained. Indeed, in the study environment, the population is forced to drink some water rich in fluoride. Fluorine is an iodine antagonist that it can easily substitute, disrupting the production of T3, T4 and TSH hormones. To end, the calculated thyroid echography volumes are for the most part normal volumes with a rate of 45.37 for boys and 35.19 for girls.